Conflict costs and economic development: Niger Delta conflict: paper presented at the Peace and Conflict: an international interdisciplinary conference at The Centre for Peace and Reconciliation Studies at Coventry University, UK. on the 17th - 20th of September 2012 - Kpagih, Leera; Tambudzai, Zachary (Midlands State University, 2016)
Economic growth is a prerequisite to economic development. Conflict is associated with costs that affect economic development levels. Identifying conflict costs could be a difficult task but the categorization of conflict costs into physical costs, human costs, social costs, natural costs and environmental costs as provided by Harris(1997) was used to determine the costs of the Niger Delta conflict. The aim of this paper is to examine the costs of conflict in the Niger Delta and the level of economic development in the region. This paper will investigate the relationship that exists between the costs of conflict and the level of economic development in the Niger Delta. The study uses development indicators such as the Human Development Index (HDI) and the Gini coefficient. Findings show that there was economic growth in the Niger Delta as the PCE level increased in the year 2004 compared to the year 1996. However, this economic growth did not lead to economic development in the Niger Delta. This is evident in the low level of human development in the region. Also the distribution of income in the region was far from equal as reflected by the gini-coefficient trends. It was found that the relationship between conflict costs and the level of economic development in the Niger Delta was negative, a sign that physical costs, human costs, social costs and natural costs of conflict all reduce the human standard of living.